2017
DOI: 10.3389/fpubh.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Low-Risk and High-Risk Human Papillomavirus Infections of the Uterine Cervix in HIV-Negative and HIV-Positive Women

Abstract: BackgroundThe prevalence, persistence, and multiplicity of human papillomavirus (HPV) infection appears different comparing HIV-positive to HIV-negative women. In this study, we examined prevalent, persistent, and multiple low- and high-risk cervical HPV infections in HIV-negative and HIV-positive women.MethodsWe studied 1,020 women involved in a study of HPV infection using SPF25/LiPA10. Two study visits were scheduled, at enrollment and 6 months afterward. At each study visit, research nurses used a cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 37 publications
(46 reference statements)
6
43
0
1
Order By: Relevance
“…More than half of HIV‐positive women positive for HPV at baseline developed persistent HPV infections, which is similar to the degree of persistence for HIV‐positive women reported from studies in South Africa and Burkina Faso . HIV‐positive women were also more susceptible than HIV‐negative women to acquire incident HPV infections, in accordance with previous studies . While the rates of AIDS‐related cancers such as Kaposi's sarcoma have decreased since the introduction of combination antiretroviral therapy (cART), a similar trend has not been observed for cervical cancer .…”
Section: Discussionsupporting
confidence: 83%
“…More than half of HIV‐positive women positive for HPV at baseline developed persistent HPV infections, which is similar to the degree of persistence for HIV‐positive women reported from studies in South Africa and Burkina Faso . HIV‐positive women were also more susceptible than HIV‐negative women to acquire incident HPV infections, in accordance with previous studies . While the rates of AIDS‐related cancers such as Kaposi's sarcoma have decreased since the introduction of combination antiretroviral therapy (cART), a similar trend has not been observed for cervical cancer .…”
Section: Discussionsupporting
confidence: 83%
“…Data suggest that HPV infections in these patients might not only occur more frequently, but that their course might also lead to faster oncogenesis [11]. It was proved in a study by Adebamowo et al, that HIV-positive females, when compared with HIV-negative subjects presented a significantly higher prevalence of lrHPV and hrHPV and a persistence of hrHPV [12]. These findings are supported by those of the meta-analysis by Looker et al, which proved that in the presence of HIV infection, the risk of HPV acquisition doubles, and for clearance halves, especially with a decline in the CD 4 cell count.…”
Section: Incidencementioning
confidence: 96%
“…Some studies suggest that in HIV-positive patients, there are additional factors, apart from immunosuppression, that contribute to the increased prevalence and persistence of HPV infections. This might be due to direct interactions of the viral genes of HIV and HPV or to changes in reactions of the cytokines in cervical mucus to HPV [12].…”
Section: Hpv Persistencementioning
confidence: 99%
“…Among the hrHPVs, HPVs 16 and 18 are the most frequently observed genotypes in patients with cervical cancer, and approximately 70% of cervical cancers are HPV 16 or 18 positive [4,16]. Several studies, including prospective cohort studies, demonstrated that the risk of HPV 16-positive patients to develop CIN2 or CIN3 lesions is higher than that reported in patients positive for other hrHPVs [12,[17][18][19]. Matsumoto et al revealed that seven hrHPV types, including HPV 16, show a high rate of progression of CIN1-2 to CIN3 compared with the other hrHPVs [12].…”
Section: Introductionmentioning
confidence: 99%